Push Notification Using the Websocket in the Application of Sistem Informasi Uji Kompetensi Online (Situk) Version 2 (Nusantara Science and Technology Proceedings, 2021)
SITUK-V2 is an application of the second version of the online competency test integrated system, which is used in the competency test at the LSP (Lembaga Sertifikasi Profesi) UPN "Veteran" Jawa Timur, with the signing up or registration process up to a statement of competence. At the time of registration, both from the session of the asesi and the asesor and the statement of graduation by the asesor, the asesi will receive a notification in the registered email, this notification uses push notification technology. Push notification technology is a technology that allows a device (client) to get information in the form of notifications sent by the information provider (server) automatically. In general, the mechanism for sending notifications from the server to the client uses a stand-alone push service (broker) and uses the Hypertext Transfer Protocol (HTTP) protocol. but in sending notifications there is often a delay to the client. In this study, a notification delivery mechanism with push notifications was developed which will be implemented using the WebSocket protocol in the SITUK-V2 application where the result is that there is a difference in delay time between the registration process and the competency statement process that is sent via user email, this is due to the influence of the size of the data, bandwidth, and device used.